The tort liability of the transmitter of viral infection in light of Algerian Legislation - Ali, Ibtissem Si (The International tax journal, 2026)
The negligence of a person infected with a contagious virus, and his failure to comply with the preventive and therapeutic measures imposed to prevent the transmission of the infection to others, may result in infecting third parties. Consequently, his tort liability arises, entailing an obligation to compensate the injured person for the damage suffered, including both actual loss and loss of profit, whether such direct damage was foreseeable or unforeseeable. However, this liability is based on fault, which must be proven by the injured party. In many cases, proving the fault of the person who transmitted the infection may be difficult, if not impossible, which may deprive the injured party of his right to compensation. This situation calls for adapting the general rules of fault-based liability and moving toward strict liability based on damage rather than fault, in order to ensure the injured party’s right to compensation.